Communication challenges faced by Libyan students in Indonesia - Mohamed AB AH Almabrok (LITERA, 2022)
Communication issue becomes one of the phenomena commonly observed among foreign students, including those studying in Indonesia. This study aims to analyze the communication challenges faced by Libyan students in Yogyakarta and their adjustment to to face the challenges. The data were from Libyan students at a number of universities in Yogyakarta, collected through questionnaire, which was designed to elicit qualitative descriptive replies. The questionnaire consists of 5 short essays and 5 yes/no questions related to the students’ experiences. The research participants were 15 Libyan male overseas students aged 21 to 35 years who joined voluntarily in this study. The findings show that the students’ competence in Bahasa Indonesia and there are two main difficulties encountered: communication issues with the local people due to the local language used by most of the local people and a gap between the students' and professors' language competency during their learning activities. Moreover, other challenges stem from varying academic workloads, teaching techniques, and assessment systems that compel international students to study as a team with the local students despite some of them lacking the ability to fluently communicate using English.